Perbandingan Efektivitas Ferric Carboxymaltose Dengan Ferrous Sulfate Sebagai Terapi Pasien Anemia Defisiensi Besi Pada Wanita Hamil - Muhammad Nafi’ Rizqi Amanillah; Muhammad Shoim Dasuki; Sri Wahyu Basuki; Supanji Raharja (Universitas Muhammadiyah Klaten, 2021)
Background: Iron deficiency anemia is still a global problem, especially in pregnant women and causes maternal death due to bleeding. This is because the need for iron increases and the food supply decreases due to improper diet and nutritional patterns before pregnancy and during pregnancy. Iron supplements are an alternative in overcoming this problem, supplements are divided into two options, namely oral and parenteral. Objective: To compare the effectiveness of Ferric carboxymaltose with Ferrous sulfate as a treatment for iron deficiency anemia in pregnant women in terms of increased hemoglobin and ferritin levels. Method: Systematic Review, this research was sourced from online databases, namely: PubMed, Science direct, Garuda ristekbrin, Google scholar and Research gate with the keywords: (